Exploring the Influence of Social Media on Deviant Sexual Behaviors Among Adolescents - Yanti Yusman; Noor Anida Zaria Mohd Noor (LKP KARYA PRIMA KURSUS, 2025)
Deviant sexual behavior among adolescents is an issue that is gaining increasing attention in the context of public health and society. This study aims to examine the influence of social media on deviant sexual behavior in adolescents aged 15–18 years. The research method used a quantitative survey with a cross-sectional design involving 500 respondents from various secondary schools. The variables analyzed included the intensity of social media use, the types of platforms used, the level of exposure to sexual content, and the level of deviant sexual behavior reported by respondents. The results showed a significant positive correlation between the frequency of social media use and deviant sexual behavior among adolescents. These findings confirm the role of social media in shaping sexual behavior patterns and underscore the need for stricter supervision and educational programs related to digital literacy and sexual health. The practical implications of this study emphasize the important role of parents, educators, and social media managers in minimizing the negative impact of social media use on adolescent sexual behavior.